PENINGKATAN KAPASITAS UMKM DALAM MENENTUKAN HARGA JUAL PRODUK MELALUI PENDAMPINGAN MANAJEMEN KEUANGAN PADA UMKM DESA WARNASARI, KABUPATEN BANDUNG - Dewanti, Yopy Ratna; Suryadi, Dedy; Bahri, Saepul; Solihin, Asep; Hidayat, Achmad (POLITEKNIK LP3I JAKARTA, 2025)
Management is an activity in the form of planning, organizing, directing and controlling as well as decision making to maximize profits. Determining the correct product cost of a product will be able to reduce uncertainly in determining the selling price. Many UMKM actors, especially in Warnasari Village, Bandung Regency with abudant potential, manage their businesses without having basic knowledge and skills regarding good business management and financial management. This activity aims toprovide understanding and knowledge to UMKM actors about the importance of good financial management and to evaluate the determination of product cost for UMKM actors using methods in the form of socialization and training as well as discussions with UMKM actors.